Geography, Structural Change and Economic Development 2009
DOI: 10.4337/9781781007754.00007
|View full text |Cite
|
Sign up to set email alerts
|

Footloose Capital and Productive Public Services

Abstract: -We analyse in a Footloose Capital productive public services provided by a central government aiming at reducing regional disparities. Two countervailing effects occur -one upon productivity and another upon local demand -the relative strength of which depends upon the financing scheme. Only if the "rich" region contributes sufficiently to the financing of the public services in the "poor" region, the poor region will actually gain. In studying these questions we pay particular attention to the dynamic adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These results are in general confirmed in the much simpler FC setting without investment sector considered by Commendatore et al (2009), where it is shown that the provision of a productivity-enhancing local public good may redistribute the industrial activity, counterbalancing differences in market sizes between regions. Furthermore, it is also confirmed that the process of agglomeration in the larger region following market integration could be slowed down or even overturned by increasing sufficiently the provision of productive public expenditure.…”
Section: Public Spending: Productivity and Demand Effectsmentioning
confidence: 53%
See 1 more Smart Citation
“…These results are in general confirmed in the much simpler FC setting without investment sector considered by Commendatore et al (2009), where it is shown that the provision of a productivity-enhancing local public good may redistribute the industrial activity, counterbalancing differences in market sizes between regions. Furthermore, it is also confirmed that the process of agglomeration in the larger region following market integration could be slowed down or even overturned by increasing sufficiently the provision of productive public expenditure.…”
Section: Public Spending: Productivity and Demand Effectsmentioning
confidence: 53%
“…In the same manner, scholars dealing with the productivity effect deliberately abstract from the demand effect. The contributions by Commendatore et al (2008Commendatore et al ( , 2009Commendatore et al ( and 2010 are at the crossroads between these two groups of models as they suggest to jointly study the interplay between the demand and productivity effects of public policy in the same framework.…”
Section: Public Spending: Productivity and Demand Effectsmentioning
confidence: 99%
“…None of the models discussed have been shown to exhibit chaotic dynamics. However, indeed, core-periphery models along the lines that have been presented here so far have been shown capable of exhibiting chaotic dynamics when in discrete form (Currie and Kubin, 2006;Commendatore, Currie, and Kubin, 2007;Commendatore, Kubin, and Petraglia, 2009;Commendatore and Kubin, 2010). While the second of these involves footloose capital between the regions, we shall look more closely at the first of these, which suggests that some of the generalizations made for the continuous model may not be robust considering a discrete version.…”
Section: Chaotic Dynamics In a Discrete Version Of The Core-peripherymentioning
confidence: 84%